Country born - Miller, Linda Lael (Miller, Linda Lael. Painted Pony Creek, 2022)
"Rancher and military veteran J.P. McCall loves simple pleasures. The satisfaction of working his family's land. The freedom to come and go as he pleases. But ever since his two closest friends have married and started families of their own, J.P. realizes what he's been missing. He's known plenty of women, but now he craves finding The One. And then Sara Worth comes crashing back into his life. She's his buddy's sister, the woman who was always out of reach. Single mom Sara Worth has her hands full. After a disastrous early marriage, she is now writing bestselling books by day and caring for her two teenagers by night. That doesn't leave a lot of me time. But when an innocent request for J.P.'s help leads to an unforgettable kiss, she's intrigued--and unsure. Giving love a second chance feels impossible. But when the man from Sara's past resurfaces, threatening everything she holds dear, J.P. will do whatever it takes to protect the woman who's stealing his heart"--